Pancreatoblastoma in children: EXPeRT/PARTNER diagnostic and therapeutic recommendations. (26th June 2021) - Bien, Ewa; Roganovic, Jelena; Krawczyk, Malgorzata A.; Godzinski, Jan; Orbach, Daniel; Cecchetto, Giovanni; Barthlen, Winfred; Defachelles, Anne‐Sophie; Ferrari, Andrea; Weldon, Christopher B.; Brecht, Ines B.; Schneider, Dominik T.; et al.
Abstract: Pancreatoblastoma (PBL) is a rare malignant epithelial neoplasm that affects typically young children. Signs related to advanced upper‐abdominal tumor accompanied by elevated serum α‐fetoprotein levels in a young child suggest PBL, however histopathological confirmation is mandatory. The mainstay of the treatment is a complete surgical resection. Unresectable and/or metastatic PBL may become amenable to complete delayed surgery after neoadjuvant chemotherapy. This manuscript presents the international consensus recommendations for the diagnosis and treatment of children with PBL, established by the European Cooperative Study Group for Pediatric Rare Tumors (EXPeRT) within the EU‐funded PARTNER (Paediatric Rare Tumors Network – European Registry) project.